Comparing self-determination theory and the L2 motivational self system and their relationships to L2 proficiency - Takahashi, Chika; Im, Seongah (Studies in Second Language Learning and Teaching, 2020)
This study empirically compares two often-utilized motivation theories in L2 studies: self-determination theory and the L2 motivational self system. It also examines the relationships among their motivational constructs, learners’ intended L2 learning effort, and L2 proficiency. While a number of studies have utilized these models in order to examine second language learners’ motivation, there has not been a thorough comparison of the two. Furthermore, while many studies have demonstrated the structural relationships between the motivational constructs of the two theories and the learner’s self-reported amount of effort, fewer studies have examined their L2 achievement. The results of this study indicated that the constituents in the two theories are correlated as predicted. Furthermore, while internalized types of motivation in self-determination theory predicted intended learning effort, which then led to L2 proficiency, the strength of the ideal L2 self was much weaker than the L2 learning experience, unlike what is argued in the theory.